Influence of microgravity on apoptosis in cells, tissues, and other systems in vivo and in vitro - Prasad, Binod; Grimm, Daniela; Strauch, Sebastian M.; Erzinger, Gilmar Sidnei; Corydon, Thomas J.; Lebert, Michael; Magnusson, Nils E.; Infanger, Manfred; Richter, Peter; Krüger, Marcus (International Journal of Molecular Sciences, 2020)
All life forms have evolved under the constant force of gravity on Earth and developed ways to counterbalance acceleration load. In space, shear forces, buoyance-driven convection, and hydrostatic pressure are nullified or strongly reduced. When subjected to microgravity in space, the equilibrium between cell architecture and the external force is disturbed, resulting in changes at the cellular and sub-cellular levels (e.g., cytoskeleton, signal transduction, membrane permeability, etc.). Cosmic radiation also poses great health risks to astronauts because it has high linear energy transfer values that evoke complex DNA and other cellular damage. Space environmental conditions have been shown to influence apoptosis in various cell types. Apoptosis has important functions in morphogenesis, organ development, and wound healing. This review provides an overview of microgravity research platforms and apoptosis. The sections summarize the current knowledge of the impact of microgravity and cosmic radiation on cells with respect to apoptosis. Apoptosis-related microgravity experiments conducted with different mammalian model systems are presented. Recent findings in cells of the immune system, cardiovascular system, brain, eyes, cartilage, bone, gastrointestinal tract, liver, and pancreas, as well as cancer cells investigated under real and simulated microgravity conditions, are discussed. This comprehensive review indicates the potential of the space environment in biomedical research.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Apoptosis; Astronauts; Cells; Cosmic radiation; Mice; Microgravity; Rats; Spaceflight; Tissues